2006
DOI: 10.1895/wormbook.1.41.1
|View full text |Cite
|
Sign up to set email alerts
|

A quick tour of nematode diversity and the backbone of nematode phylogeny

Abstract: Contrary to textbook dogma, nematodes are not only highly diverse, but often also complex and biologically specialized metazoans. Just a few of the many fascinating adaptations are reviewed in this chapter, as a prelude to a quick tour through phylogenetic relationships within the phylum. Small Subunit rDNA sequences have confirmed several controversial prior hypotheses, as well as revealing some unexpected relationships, resulting in a recent proposal for revised classification. Three major lineages exist wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 12 publications
0
57
0
10
Order By: Relevance
“…Alternatively, they might represent regulatory pathways that are unique to C. elegans owing to its evolutionary history. Regarding the latter point, although this information might not be directly relevant to human health, it could be useful for the control of parasitic nematodes, which share a high degree of similarity with C. elegans (De Ley, 2006). Finally, the neuroendocrine system also affects the function of B and T cells of the adaptive immune system, and molecular insights into the antigen-specific immune responses in which these cell types are involved can only be gained from studies of higher vertebrates.…”
Section: Limitations Of the C Elegans Model For Studying Neuroimmunementioning
confidence: 99%
“…Alternatively, they might represent regulatory pathways that are unique to C. elegans owing to its evolutionary history. Regarding the latter point, although this information might not be directly relevant to human health, it could be useful for the control of parasitic nematodes, which share a high degree of similarity with C. elegans (De Ley, 2006). Finally, the neuroendocrine system also affects the function of B and T cells of the adaptive immune system, and molecular insights into the antigen-specific immune responses in which these cell types are involved can only be gained from studies of higher vertebrates.…”
Section: Limitations Of the C Elegans Model For Studying Neuroimmunementioning
confidence: 99%
“…According to Coomans (2002), morphology can still provide useful diagnostic characters, especially if we are able to overcome the limited resolution light microscopy provides. And despite all its limitations, morphology-based study when carried out diligently can be as good as any biochemical or molecular method used in identifying taxa (Mayr and Ashlock, 1991;De Ley, 2006;Agatha and Strüder-Kypke, 2007). What is lacking, however, is the technical and taxonomic expertise required to correctly utilise phenotypic characters to effectively make a decision about the identity of an organism .…”
Section: Classical Taxonomymentioning
confidence: 99%
“…nanus-like' configuration, in order to avoid compensatory migrations and to speed up the cell cycle periods and thereby developmental rate. However, recently Lahl et al (2003) observed a reversal of polarity in P 2 and P 3 in several species of the Plectidae, an outgroup of the Rhabditida (Blaxter et al, 1998;De Ley & Blaxter, 2002;Meldal et al, 2007). Furthermore, descriptions of the early development of members of other families from clades I, II and III suggest the presence of small primordial germ precursor cells at the ventral side that contact the intestinal precursor (Malakhov, 1994).…”
Section: Reversal Of Polarity In the Germlinementioning
confidence: 99%
“…Throughout this order, the adult body plan has undergone a wide range of evolutionary modifications that allows them to flourish in terrestrial habitats, e.g., those subject to frequent episodes of rapid de-and rehydration, such as mosses and lichens or extremely xeric and/or cryogenic soils (De Ley, 2006). For example, adaptations in buccal and pharynx morphologies and different food strategies for different adult species must occur late in development after all cells are formed in the first part of embryonic development.…”
Section: Embryonic Cell Lineage Conserved Within Clades 9 and 10mentioning
confidence: 99%
See 1 more Smart Citation